El Derecho y su enseñabilidad -sobre la necesidad de una reflexión académico-jurídica- - Tovar, Luis Freddyur (2023)
Social groups converge upon particular normative orders; therefore, legal education is especially important in any society, insofar as it produces and reproduces that societyís legal consciousness. Currently, law can be understood in two ways, both of which have negative connotations: first, for Marxist theories it is an apparatus of domination, a form of power imposed by the elites, even through the use of force, a power from which societies crave to free themselves; second, law is seen as a preserver of the status quo, and its product is a conservative society that justifies all of its actions through the existence of a formal legal order, thereby rendering law into an obstacle to higher purposes. This article wants to solve this confusion by reflecting upon legal practice in Colombia. The author proposes that the content, practice, and teaching of law be reformed, so that legal education can allow legal practice to face the challenges posed by todayís world, a world that rejects any kind of dogmatic reasoning.